The Contribution of the Fouchet Commission to the Fouchet Negotiations: European diplomacy in the 1960s and the battle between supranationalism and intergovernmentalism - Lee, Cas van der (Student Undergraduate Research E-journal!, 2017)
The struggle between supranational and intergovernmental visions on European integration came to dramatic heights with the little-known battle over the Fouchet Plan in 1961-62. This study examines the internal negotiations within the Fouchet Commission, its share in the failure of the Fouchet Plan and how national politicians and interests shaped its negotiations. Thanks to new archival research the understudied influence of the Fouchet Commission has been scrutinised, which provides a new perspective on the failure of the Fouchet Plan, namely the evasion of the members of the Fouchet Commission to discuss fundamental principles as well as their incompetence in reaching compromises, and on the process of European integration, i.e. the decisive role played by national politicians. This supports the integration theory of intergovernmentalism and asks fundamental questions about the role national actors play in European integration. The recent election of French president Emmanuel Macron has given a new impulse to the process of European integration, indicating that besides the European institutions, national politicians play an important role in shaping European integration.